Compassionate use of tezepelumab in near fatal asthma: A case report and review of the literature - Mako Nakajima; Masashi Matsuyama; Yuki Yamazaki; Hiroya Sunabe; Yuta Takahashi; Keishun Boku; Takeshi Miura; Tomohiro Tamura; Yoshiaki Inoue; Nobuyuki Hizawa (Respiratory Medicine Case Reports)
A 38-year-old man with near fatal asthma requiring intubation and invasive mechanical ventilation (IMV) was transferred to our hospital. Veno-venous extracorporeal membrane oxygenation (VV-ECMO) was initiated due to hypotension and mediastinal emphysema secondary to barotrauma. Since high-dose systemic corticosteroid therapy failed to relieve the severe bronchospasm, a single dose of tezepelumab was administered on a compassionate basis. This intervention resulted in successful extubation 7 days later. This is a rare case in which a biologic agent was used as a rescue therapy for near fatal asthma. This case is presented along with a review of the relevant literature.